The Role of Social Media Influencers in Increasing Tourists’ Visit Intention in Indonesian Marine National Park - Pratomo, Luki Adiati; Rahayu, Fatik; Siregar, Raymond; Rahayu, Dwi Hartini; Risde, Kahti Ramadhia; Lisanti, Prameshwari Dinda (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
This study aims to determine the role of influencers in encouraging tourists’ desire to visit the Indonesian Marine National Park. This research will measure the influencer’s source characteristics and subjective norms influencing attitudes toward marketing communication and risk perception. Finally, it will investigate the effect of risk perception on tourists’ visit intention. 190 respondents of consumers familiar with tourism influencers serve as the data for the analysis of covariant-based SEM. This research finds that source characteristics and subjective norms positively influence attitudes toward marketing communication. Attitude toward marketing communication does not affect the perceived risk of consumers. Otherwise, the perceived threat does not affect consumer visit intention. Implications and further research are provided.